2017
DOI: 10.1002/hec.3580
|View full text |Cite
|
Sign up to set email alerts
|

Employment insecurity and employees' health in Denmark

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
0
33
1
Order By: Relevance
“…Finally, 7 (13.0%) studies considered the role of social and family support for workers in the association. In 2 cases [40,41], it was introduced as a confounder variable in the regression models and no further explanation was given. In 2 studies [42,43], social support variables were found to have no impact on the association, while the other 3 studies demonstrated that social and family support as well as the household situation decreased the impact of precarious employment (1 study, [19]), income and employment quality [44] and restructuring processes (1 study, [45]) on mental health.…”
Section: Causal Pathwaysmentioning
confidence: 99%
“…Finally, 7 (13.0%) studies considered the role of social and family support for workers in the association. In 2 cases [40,41], it was introduced as a confounder variable in the regression models and no further explanation was given. In 2 studies [42,43], social support variables were found to have no impact on the association, while the other 3 studies demonstrated that social and family support as well as the household situation decreased the impact of precarious employment (1 study, [19]), income and employment quality [44] and restructuring processes (1 study, [45]) on mental health.…”
Section: Causal Pathwaysmentioning
confidence: 99%
“…Whereas job insecurity represents concerns about involuntarily losing one’s current job, employment insecurity represents the perceived likelihood of not finding comparable new employment in the event of job loss (e.g., Y. Cheng, Huang, Li, & Hsu, 2011; Chung & van Oorschot, 2011; Cottini & Ghinetti, 2018; European Foundation for the Improvement of Living and Working Conditions, 2008; Kuhnert & Vance, 1992; Muffels & Wilthagen, 2013). 2 Although models of job insecurity (Probst, 2005; Shoss, 2017) have not directly addressed the potential for macroeconomic events to increase employment insecurity, such an association is consistent with Pearlin and Bierman’s (2013) model of stress.…”
Section: Net Effects Of the Great Recessionmentioning
confidence: 99%
“…Silla, De Cuyper, Gracia, Peiro, and De Witte (2009) found that job insecurity was positively related to psychological distress and life dissatisfaction, but the associations involving employment insecurity were not significant. Cottini and Ghinetti (2018) used panel data and found that job insecurity and employment insecurity were simultaneously negatively associated with mental health, but only employment insecurity was negatively related to reported energy/vitality. Based on this discussion and the limited data on the simultaneous associations of job and employment insecurity to mental health, and no research on physical health, the following hypotheses are proposed:…”
Section: Mediating Role Of Job and Employment Insecuritymentioning
confidence: 99%
“…Previous research indicates that perceived job insecurity is a stressor, which is therefore positively correlated to poorer mental well-being, in general, and anxiety, in particular (Simmons and Swanberg, 2008;Burgard et al, 2009;Milner et al, 2016;Cottini and Ghinetti, 2018;Wood and Burchell, 2018). For instance, Simmons and Swanberg (2008) found that job insecurity is the single most significant correlate of depressive symptoms for working poor employees.…”
Section: Literature Review and Research Propositionsmentioning
confidence: 99%
“…Economic and political variables (such as labor market regulation, employment protection legislation, welfare policies, unemployment rate) as well as prevailing cultural frameworks could predict diversity in health-related outcomes of the experience of job insecurity (Erlinghagen, 2008;László et al, 2010;Balz, 2017). Nonetheless, most research in the field has so far investigated single countries, such as UK (Ferrie et al, 2005), Germany (Reichert and Tauchmann, 2017), Spain (Menéndez-Espina et al, 2019), Finland (Griep et al, 2016), Denmark (Cottini and Ghinetti, 2018), the United States (Simmons and Swanberg, 2008), Japan (Kachi et al, 2018), Australia (Green, 2011), and Canada (Wang et al, 2008). Even the studies of Buffel et al (2015) and Caroli and Godard (2016), whose analyses drew on large and international datasets, have not provide crosscountry comparative analyses.…”
Section: Introductionmentioning
confidence: 99%